Evaluation of Physicochemical Characteristics of Water in Warangal District, Telangana, India - Bairi, Navya Sri; Beesam, Srinu; Kondampati, Kasturi Devi (Science and Technology: Developments and Applications Vol. 9, 2025)
Water quality is essential for ensuring safe usage in domestic and agricultural applications, particularly in regions with intensive farming activities. Contaminated water sources can result in severe waterborne diseases that affect human health. Limited research exists on poultry farm water sources in Warangal district, leaving gaps in understanding long-term contamination impacts on human and animal health. Therefore, the research aimed to assess the physiochemical contamination in the groundwater. In the Warangal district of Telangana, 100 water samples for a period of 6 months from poultry farms were analyzed to assess key physiochemical parameters, including pH, temperature, electrical conductivity, total dissolved solids (TDS), salinity, redox potential, and hardness. The physiochemical parameters were analyzed using a digital water analysis kit. Data collected for all the water quality parameters were arranged and subjected to descriptive statistical analysis. This study revealed significant variations in water quality throughout the Warangal district of Telangana, highlighting important issues such as pH levels, total dissolved solids (TDS) and hardness that exceed the permissible limits as indicated by the Bureau of Indian Standards (BIS: IS 3025). The results showed considerable variability, with pH values ranging from 4.82 to 9.28, indicating both acidic and alkaline conditions. Conductivity ranged from 48 to 940 µS/cm, while TDS levels varied between 48 and 1470 ppm, with some samples exceeding permissible limits. Salinity and hardness fluctuations raised concerns about water suitability for consumption and irrigation. Correlation analysis revealed strong positive relationships between salinity and TDS (r = 0.627, p < 0.01) and between conductivity and redox potential (r = 0.614, p < 0.01), highlighting the interdependence of dissolved ions and oxidation-reduction processes. Additionally, moderate correlations were observed between TDS and both conductivity (r = 0.407, p < 0.01) and pH (r = 0.346, p < 0.05). These findings emphasize the necessity of ongoing monitoring and strategic water treatment measures to safeguard water quality and ensure its safe and sustainable use. Addressing these concerns requires a comprehensive approach that includes technological advancements, regulatory measures and public awareness campaigns. Further studies on contamination sources are needed to develop effective water management strategies.